Granulocyte Colony-Stimulating Factor Treatment Before Radiotherapy Protects Against Radiation-Induced Liver Disease in Mice - Ramos, Isalira Peroba Rezende; Dias, Marlon Lemos; Nunes De Moraes, Alan Cesar; Meireles Ferreira, Fernanda Guimarães; Souza, Sergio Augusto Lopes; Gutfilen, Bianca; Barboza, Thiago; Ferreira Pimentel, Cibele; Paz Batista, Cintia Marina; Kasai-Brunswick, Tais Hanae; Fortes, Fabio Da Silva De Azevedo; De Andrade, Cherley Borba Vieira; et al. (Frontiers in Pharmacology, 2021)
Radiation-induced liver disease (RILD) remains a major problem resulting from radiotherapy. In this scenario, immunotherapy with granulocyte colony-stimulating factor (G-CSF) arises, such as an attractive approach that might improve the injured liver. Here, we investigated G-CSF administration's impact before and after liver irradiation exposure using an association of alcohol consumption and local irradiation to induce liver disease model in C57BL/6 mice. Male and female mice were submitted to a previous alcohol-induced liver injury protocol with water containing 5% alcohol for 90 days. Then, the animals were treated with G-CSF (100 µg/kg/d) for three days before or after liver irradiation (18Gy). At days 7, 30, and 60 post-radiation, non-invasive liver images were acquired by ultrasonography, magnetic resonance, and computed tomography. Biochemical and histological evaluations were performed to verify whether G-CSF prevents liver tissue damage and could reverse the acute liver injury. Our data showed that the treatment with G-CSF before irradiation effectively improved morphofunctional parameters caused by RILD, restoring histological arrangement, promoting liver regeneration, preserving normal organelles distribution, and glycogen granules. The amount of OV-6 and F4/80-positive cells increased, and α-SMA positive cells' presence was normalized. Additionally, prior G-CSF administration preserved serum biochemical parameters and increased the survival rates (100%). On the other hand, after irradiation, the treatment showed a slight improvement in survival rates (79%) and did not ameliorate RILD. Overall, our data suggest that G-CSF administration before radiation might be an immunotherapeutic alternative to radiotherapy planning to avoid RILD